PENGARUH EDUKASI MENYUSUI TERHADAP PENGETAHUAN DAN SELF EFFICACY PRIMIGRAVIDA - I Komang Lindayani; Ni Made Dwi Purnamayanti (Siklus : Journal Research Midwifery Politeknik Tegal, 2023)
There are still many mothers who have not been able to provide breast milk to their babies for various reasons that cause the failure of exclusive breastfeeding. The prior study show that knowledge and self-efficacy were factors that cause failure of mothers to breastfeed. This study aims to examine the effect of breastfeeding education on primigravid knowledge and self-efficacy. This research is a quantitative study using a quasi-experimental design with a pre and post with a control group approach. The research was conducted in June - August 2022, in three Public Health Center at Denpasar City. The sampling technique used purposive sampling with a sample size of 66 respondents. The results showed that there was a significant difference between knowledge and self-efficacy before and after treatment with p-value 0.05. Likewise, there is a significant difference between knowledge and self-efficacy before and after in the 2 groups. This shows that breastfeeding education has an effect on increasing knowledge and self-efficacy of primigravidas. Knowledge must be built comprehensively since pregnancy so mother is ready to breastfeed. In addition, knowledge is also related to the formation of self-efficacy. More intensive efforts are needed from health facilities and health workers in providing breastfeeding education.Keywords: Breastfeeding Education, Knowledge and Self Efficacy